The Validity Analysis of English Summative Test of Junior High School - Baiq Della Triastiwi Putri (Universitas Pendidikan Mandalika, 2018)
This research was aimed at analyzing the English summative test validity at SMP Darul Hamidin Padamara. The object of the research was the English summative test given to seventh grade students in the academic year 2016/2017 used descriptive method. The instrument used to analyze the data is documentation such as the English summative test, syllabus, blueprint and students answer sheet. The researcher matched the English summative test and syllabus to find out the content validity, for construct validity the researcher use blueprint and the last is students answer sheet to find out the criterion validity, to support the data the researcher used questionnaire. The finding of this research showed that the English summative test of SMP Darul Hamidin had validity in term of content and construct validity because 96% of test matched with indicators and for criterion validity was not valid because out of 50 items only 10 items were valid.